2008
DOI: 10.1074/jbc.m804392200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulating Sphingosine 1-Phosphate Receptor-2 Signaling Impairs Chemotactic, Wound-healing, and Morphogenetic Responses in Senescent Endothelial Cells

Abstract: Vascular endothelial cells (ECs) have a finite lifespan when cultured in vitro and eventually enter an irreversible growth arrest state called "cellular senescence." It has been shown that sphingolipids may be involved in senescence; however, the molecular links involved are poorly understood. In this study, we investigated the signaling and functions of sphingosine 1-phosphate (S1P), a serum-borne bioactive sphingolipid, in ECs of different in vitro ages. We observed that S1P-regulated responses are significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 50 publications
2
58
1
Order By: Relevance
“…Recently, we showed that early-passaged ECs in vitro abundantly express S1P 1 receptors and barely express S1P 2 receptors. In contrast, S1P 2 receptors are markedly increased in senescent ECs (9). The upregulation of S1P 2 receptors was shown to mediate the impaired wound-healing and angiogenic responses in senescent ECs (9).…”
Section: ϫ4mentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, we showed that early-passaged ECs in vitro abundantly express S1P 1 receptors and barely express S1P 2 receptors. In contrast, S1P 2 receptors are markedly increased in senescent ECs (9). The upregulation of S1P 2 receptors was shown to mediate the impaired wound-healing and angiogenic responses in senescent ECs (9).…”
Section: ϫ4mentioning
confidence: 98%
“…Thus cultured young and senescent ECs were used as an in vitro model to examine whether endothelial S1P 1 -and S1P 2 -mediated signaling cascades are able to concertedly regulate vascular barrier function in vivo. A minimal rise of TEER, an in vitro measurement of endothelial barrier function (9,17), in senescent ECs after S1P treatment is shown in Fig. 8A.…”
Section: ϫ4mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed that endogenous S1P 2 mediated inhibition of Rac activity, cell migration, and capillary-like tube formation in an EC line and that an S1P 2 -selective antagonist enhanced in vivo angiogenesis in Matrigel plug assays (26). In addition, using both in vitro and in vivo models, several other groups have shown the antiangiogenic activity of S1P 2 receptor (27,28). However, it remains unknown whether and how S1P 2 is involved in tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the overexpression of S1P2 exaggerates these S1P-induced responses in ECs. In senescent ECs, S1P2 is upregulated, which leads to inhibition of migration and tube formation in vitro [41] . Therefore, it is an intriguing possibility that S1P2 might play an inhibitory role in angiogenesis, which contrasts with S1P1.…”
Section: S1p In Vascular Formationmentioning
confidence: 99%